Effect of Community Support Agents on Retention of People Living With HIV in Pre-antiretroviral Care: A Randomized Controlled Trial in Eastern Uganda. (1st October 2015) - Lubega, Muhamadi; Tumwesigye, Nazarius Mbona; Kadobera, Daniel; Marrone, Gaetano; Wabwire-Mangen, Fred; Peterson, Stefan; Reynolds, Steven J.; Ekström, Anna Mia
Abstract : Background: Over 50% of people living with HIV (PLHIV) in sub-Saharan Africa are lost to follow-up between diagnosis and initiation of antiretroviral treatment during pre-antiretroviral (pre-ARV) care. The effect of providing home counseling visits by community support agents on 2-year retention in pre-ARV care was evaluated through a randomized controlled trial in eastern Uganda. Methods: Four hundred newly screened HIV-positive patients were randomly assigned to receive posttest counseling alone (routine arm) or posttest counseling and monthly home counseling visits by community support agents to encourage them go back for routine pre-ARV care (intervention arm). The outcome measure was the proportion of new PLHIV in either arm who attended their scheduled pre-ARV care visits for at least 6 of the anticipated 8 visits in the first 24 months after HIV diagnosis. The difference between the 2 study arms was assessed using the χ 2 and T tests. Mantel–Haenszel Risk Ratios and multivariate logistic models were used to assess the adjusted effect of the intervention on the outcome. Results: In all models generated, participants receiving monthly home counseling visits were 2.5 times more likely to be retained in pre-ARV compared with those in standard care over a period of 24 months (adjusted risk ratio, 2.5; 95% confidence interval: 2.0 to 3.0). Conclusion: Monthly follow-up home visits by community workers more than doubled the retention of PLHIV in pre-ARV care in rural Uganda and can be applicable in similar resource-poor settings. Abstract : Supplemental Digital Content is Available in the Text.